Perimenopausal and Postmenopausal Endometrial Hyperplasia - Łukaszek, Stanisław (Menopause Review/Przegląd Menopauzalny, 2003)
Abnormal proliferations of the endometrium may cause not only unpleasant clinical symptoms, but may be an early stage of carcinogenesis as well. The risk of the carcinoma can be so high that a radical treatment is necessary. Since the only definite method of diagnosis is the microscopic examination of the endometrium, a close cooperation of the gynecologist and the pathologist is essential. The proper sampling of the endometrium, the knowledge of different forms of the endometrial hyperplasia, and the accurate interpretation of the pathological diagnosis are crucial for the adequate therapy.